CONCEPÇÕES E PRÁTICAS O DILEMA DA AVALIAÇÃO DA APRENDIZAGEM: Um estudo de caso da prática avaliativa de professores da rede estadual de ensino do maranhão - Machado, Silvana Maria Guimarães (2006)
The present research analyzes the evaluation of the learning for beyond a study of practice, searching clarifying elements in the scientific study of the knowledge. Investigation action has the purpose to unveil what it is underlying to the testing practices that contribute for the failure pertaining to school and social exclusion of the fellows. At the same time, it searches to raise proposals and theoretician-methodologies orientations, in a dialectic and hysterical-critic and boarding, pointing out the evaluation in favor of the learning s.